Role of Plasma D-Dimers in the Diagnosis of Thrombotic Events in Patients with Chronic Coronary Heart Disease - Yu. V. Nikiforov; G. G. Chernysheva; O. V. Vukolova; L. V. Molchanova; M. Ye. Yevdokimov (Общая реаниматология, 2006)
Objecive: to estimate hemostatic parameters in 15 cardiosurgical patients with chronic coronary heart disease. Ten parameters of the hemostatic system were determined at 4 stages. The patients were divided into 2 groups in relation to the baseline level of D-dimers. The study demonstrated that hypercoagulation and depressed fibrinolysis retained despite the baseline coagulative potential and the performed therapy in all the patients before discharge. It is obvious that the standard approaches to diagnosing hemostatic disorders and correcting them should be revised.